Dobutamine promotes the clearance of erythrocytes from the brain to cervical lymph nodes after subarachnoid hemorrhage in mice - Wang, Xue; Deng, Hong-Ji; Gao, Sheng-Qing; Li, Tao; Gao, Chao-Chao; Han, Yan-Ling; Zhuang, Yun-Song; Qiu, Jia-Yin; Miao, Shu-Hao; Zhou, Meng-Liang (Frontiers in Pharmacology, 2023)
Background: Erythrocytes and their breakdown products in the subarachnoid space (SAS) are the main contributors to the pathogenesis of subarachnoid hemorrhage (SAH). Dobutamine is a potent β1-adrenoreceptor agonist that can increase cardiac output, thus improving blood perfusion and arterial pulsation in the brain. In this study, we investigated whether the administration of dobutamine promoted the clearance of red blood cells (RBCs) and their degraded products via meningeal lymphatic vessels (mLVs), thus alleviating neurological deficits in early stage post-SAH. Materials and methods: Experimental SAH was induced by injecting autologous arterial blood into the prechiasmatic cistern in male C57BL/6 mice. Evans blue was injected into the cistern magna, and dobutamine was administered by inserting a femoral venous catheter. RBCs in the deep cervical lymphatic nodes (dCLNs) were evaluated by hematoxylin-eosin staining and the hemoglobin content in dCLNs was detected by Drabkin’s reagent. The accumulation of RBCs in the dura mater was examined using immunofluorescence staining, neuronal death was evaluated by Nissl staining, and apoptotic cell death was evaluated by TUNEL staining. The Morris water maze was used to examine the cognitive function of mice after SAH. Results: RBCs appeared in dCLNs as early as 3 h post-SAH, and the hemoglobin in dCLNs peaked at 12 h after SAH. Dobutamine significantly promoted cerebrospinal fluid drainage from the SAS to dCLNs and obviously reduced the RBC residue in mLVs, leading to a decrease in neuronal death and an improvement in cognitive function after SAH. Conclusions: Dobutamine administration significantly promoted RBC drainage from cerebrospinal fluid in the SAS via mLVs into dCLNs, ultimately relieving neuronal death and improving cognitive function.